2004
DOI: 10.1055/s-2004-814555
|View full text |Cite
|
Sign up to set email alerts
|

Management of Malignant Strictures of the Cervical Esophagus with a Newly-Designed Self-Expanding Metal Stent

Abstract: Recently, the use of self-expanding metal stents has become a well-established method of palliative treatment for stenotic malignant diseases in the middle and distal esophagus. However, published results on the use of self-expanding metal stents in cervical esophageal cancer are somewhat limited by a paucity of clinical details and experience. A new self-expanding esophageal metal stent with a short upper flange 0.7 cm in length was studied prospectively in order to assess its efficacy for palliative treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…However, Verschuur et al found similar morbidity and recurrent dysphagia in patients with cervical and thoracic/abdominal esophageal stents [46]. Specific stents have been designed for the cervical esophagus, for example the ''Ultraflex'' (Boston Scientific) with a low radial expansion force [47], with a small proximal collar (5 mm) to reduce gastroesophageal reflux [48], or with a proximal delivery system in order to secure correct positioning of the stent (MITech Co, Pyontack, South Korea) [49]. Only a few rare cases of tracheal compression due to esophageal stent have been reported [50].…”
Section: Resultsmentioning
confidence: 99%
“…However, Verschuur et al found similar morbidity and recurrent dysphagia in patients with cervical and thoracic/abdominal esophageal stents [46]. Specific stents have been designed for the cervical esophagus, for example the ''Ultraflex'' (Boston Scientific) with a low radial expansion force [47], with a small proximal collar (5 mm) to reduce gastroesophageal reflux [48], or with a proximal delivery system in order to secure correct positioning of the stent (MITech Co, Pyontack, South Korea) [49]. Only a few rare cases of tracheal compression due to esophageal stent have been reported [50].…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this, Dr Shim modified the SEMS with a smaller diameter funnel-shape proximal end. 1,2 In comparison with the standard SEMS, it has a shorter length of the proximal funnel (7 mm vs. 20 mm) and a narrower fully expanded diameter (18 mm vs. 20 mm). The modification decreases UES compromise and foreign body sensation.…”
Section: Discussionmentioning
confidence: 99%
“…The modification decreases UES compromise and foreign body sensation. 2 Our patient was treated first with a Niti-S stent because there was no modified SEMS available in Taiwan. The proximal end of the SEMS was placed at 20 cm from the incisor and achieved successful coverage of the TE fistula initially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the placement of a stent in the cervical esophagus has traditionally been restricted because of the risk of potential adverse events such as tracheal compression, proximal migration, intractable pain and, most commonly, foreign body sensation (10,11). Nevertheless, some reports have suggested the possibility of treating this type of stricture by placing a stent in the cervical esophagus (12).…”
Section: Introductionmentioning
confidence: 99%